DAKWAH MELALUI PEMBINAAN KEAGAMAAN TERHADAP MASYARAKAT MUSLIM PEDALAMAN OLEH PENYULUH AGAMA ISLAM NON PNS KECAMATAN TEBAS, SAMBAS - Herles Anwar; Mualimin Mualimin (Jurnal Bimbingan Penyuluhan Islam, 2019)
Tebas District is part of the 3 T region which has the largest population in Sambas district. Most of the population in the Tebas sub-district are spread in 23 villages where transportation access is quite alarming. This reality is not balanced with the number of non PNS Islamic religious instructors appointed by the Ministry of Religion, which amounted to only three people in 2019. Despite having limited personnel, the propaganda carried out with religious guidance was able to touch all circles and entire Tebas sub-district. This study aims to analyze da'wah through religious guidance carried out by Islamic religious instructors in the Tebas sub-district which is in the interior (3 T). This study is a field research using qualitative methods. The results of the analysis of the research findings can be concluded that the religious guidance carried out by Islamic religious instructors in the Tebas sub-district of Sambas district still uses a conventional coaching approach that emphasizes the delivery of da'wah messages orally and directly. Nonetheless, non-PNS Islamic religious instructors in Tebas district, Sambas district, their guidance efforts were carried out with a "pick up ball" pattern and were systematically scheduled. The selection of the guidance approach is based on the social reality of the missionary objectives that are still lagging behind both in terms of technology, access to information and transportation, and limited personnel resources in conducting guidance.